Sistem Pendukung Keputusan Penentuan Profesi Linier Untuk Lulusan Program Studi Sistem Informasi Dengan Metode SAW (Retii, 2019)
We are facing the era of the industrial revolution 4.0. Technology disruption in all fields, labor/vacanciesand unemployment are important issues today. The Ministry of Research, Technology and Higher Educationand the Ministry of Manpower in 2017 have stated that the suitability level of the workforce profession withmajors/courses during college is still relatively low at 45%. On the other hand, the National AccreditationAgency for Higher Education (BAN-PT) when assessing the study program also measures the degree oflinearity between the competencies of graduates with the occupational profession. For this reason, a decisionsupport system exists as a solution to the problems mentioned above. Based on the IS Curriculum 2010document, the SAW (Simple Additive Weighting) method has been implemented by determining 17alternatives/professions and 18 criteria/competencies (consisting of 3 levels: significant coverage, somecoverage, not required). This system has successfully produced output in the form of a ranking of professionsthat are most relevant to the competencies of Information Systems graduates.Keyword : decission support, SAW, profession, information system